Pengaruh Konsep Diri terhadap Asertivitas Siswa SMA Negeri 15 Padang - Firdaus, Hariandi Viky; Rusli, Devi (Lembaga Yasin AlSys, 2025)
Socialization is one of the human social developments. Social development refers to an individual's ability to behave or act in interactions with social elements in society that meet social demands. The elements of socialization in society include family, friends, school, and mass media. In the school environment, students learn to build relationships with their peers from various family social statuses. To face the problems in the school environment, students must be brave in expressing their feelings and opinions, which is often referred to as assertiveness. This study aims to determine the influence of self-concept on assertiveness in students at SMA Negeri 15 Padang. This research uses a quantitative method. The population in this study consists of 700 students from classes XI and XII at SMA Negeri 15 Padang. Sampling was conducted using purposive sampling with 140 respondents. The study used self-concept and assertiveness scales as measuring instruments. Data analysis was performed using simple regression analysis with IBM SPSS 27. The results of the hypothesis testing showed a significance value (Sig.) of 0.001 < 0.05 with a coefficient of 0.425 and an R Square value of 0.181, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that there is a positive influence of self-concept on assertiveness among students at SMA Negeri 15 Padang, with an effect size of 18.1%, while the remaining influence is shaped by other factors such as gender, parenting style, culture, and social economic status. In conclusion, the higher the self-concept, the higher the assertiveness.